EFFORTS TO INCREASE THE SAMAPTA UNIT PATROL UNIT FOR THE PREVENTION OF THEFT OF MOTOR VEHICLES IN THE JURISDICTION OF THE DEMAK POLICE - JHONATHAN ROGANDA SITORUS JHONATHAN (Police Studies Review, 2022)
This research was motivated by the rise of motor vehicle theft cases in the jurisdiction of the Demak Police. Police need to carry out patrol actions to prevent the meeting of the intentions and opportunities of criminals, especially in curanmor. Therefore, the purpose of this study is to describe the efforts of samapta unit patrol units and factors that affect the implementation of patrols and the efforts increased by the Demak Police samapta unit through patrols in order to prevent theft. motor vehicles. This type of research uses a field of research and a qualitative approach. Data sources include primary data and secondary data with data collection techniques used are interviews, observations, and document studies Data analysis techniques used include data reduction, data presentation and conclusion drawing. Knife analysis in conducting discussions includes management theory and SWOT theory The results of the study found that curanmor crimes had fluctuated over the past 3 years, patrol activities carried out by the Samapta Unit of the Demak Police were carried out according to the SOP, divided into 3 stages, namely preparation, implementation stage and termination stage. Judging from several aspects, it is considered less than optimal for patrol implementation in samapta influenced by several factors. The most influential internal factors are inadequate and external facilities and infrastructure are the jurisdiction of the Demak Police which is quite wide and the intentions of criminals are difficult to predict. The improvement efforts carried out by the Patrol Unit samapta Demak Police are through the Jaga Wali patrol launched by the Police Chief demak AKBP Budi Adhy Buono, S.I.K., M.H. namely by carrying out patrols carried out by all technical functions of the police in demak police. Based on the results of the study, the author suggests that in the creation of patrol routes always pay attention to the development of the last Kamtibmas situation in Kabupaten Demak, implementing a special budget for patrol units. Often establish cooperation with the community, such as Hansip post, Kamra post, Security Guard post, and Kamling post selectively to facilitate monitoring locations prone to theft of motor vehicles and patrols through residential areas of the community.